Development of a Synectic Model in Speeching Learning In Class - Wiarsih, Asih (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2023)
Giving a speech is a form of communication that is widely used for various purposes and can support a person's success.Through learning to give speeches, students are expected to be able to convey thoughts, ideas and thoughts to teachers, friends and other people. Speech activities can also foster feelings of self-confidence and courage to appear in public. Speech skills are skills that are difficult for students to master. Therefore, it is necessary to develop a learning model that can improve students' speech skills, one of the models that the author developed is the synectic model. The problems contained in this research are1) What is the design of the synectic model developed in speech learning for class XI students at the Ciwaringin Islamic Boarding School, Cirebon Regency? 2) How effective is the synectic model in teaching speech for class XI students at the Ciwaringin Islamic Boarding School, Cirebon Regency? 3) What is the profile of the oratory skills of class XI students at the Ciwaringin Islamic Boarding School, Cirebon Regency?It is hoped that the results of this research can provide input for Indonesian language subjects, especially in learning speech. SampleIn this research there were 27 students in class XI of the Ciwaringin Islamic Boarding School, Cirebon Regency. The data collection techniques used in this research are: (1) library techniques (2) test techniques: a. Initial test (pretest) b. Final test (post test). Based on the discussion of research results, data interpretation, and hypothesis testing, the following conclusions were obtained: (1) the ability of Class IX students at the Ciwaringin Islamic Boarding School, Cirebon Regency, in making speeches before learning using synectic development was relatively low. Based on calculations, the percentage only reached 61.9% or more than half did not have the ability to make a speech. (2) the ability of Class. Based on calculations, the percentage reached 72.6% or almost all of them had the ability to make speeches. (3) The use of the development of the synectic model in learning speeches in class Based on the results of product moment correlation test calculations, it is known that r = 0.884 or 88.4% and based on the interpretation table, it is considered a very strong correlation..Thus, it can be concluded that the development of the synectic model is able to improve students' speech skills.